THE TUMOR MACROENVIRONMENT: CANCER-PROMOTING NETWORKS BEYOND TUMOR BEDS - Rutkowski, Melanie R. (Adv Cancer Res, 2015)
During tumor progression, alterations within the systemic tumor environment, or macroenvironment, result in the promotion of tumor growth, tumor invasion to distal organs, and eventual metastatic disease. Distally produced hormones, commensal microbiota residing within mucosal surfaces, and myeloid cells and even the bone marrow impact the systemic immune system, tumor growth, and metastatic spread. Understanding the reciprocal interactions between the cells and soluble factors within the macroenvironment and the primary tumor will enable the design of specific therapies that have the potential to prevent dissemination and metastatic spread. This chapter will summarize recent findings detailing how the primary tumor and systemic tumor macroenvironment coordinate malignant progression.